Criminal Law Enforcement in The Financial Services Sector in Case of Insurance Companies That Have Defaulted - Wardhani, Indah Kusuma (CV. Publikasi Indonesia, 2024)
At this time, many cases of insurance companies have defaulted so that policyholders have difficulty getting compensation payments when an uncertain event occurs. Moreover, this default case occurs in large insurance companies which makes public trust in insurance companies reduced. Of these various cases, one of the causes is the weak supervision and law enforcement in the financial services sector carried out by the Financial Services Authority (OJK). The purpose of this study is to analyze the enforcement of criminal acts in the financial services sector in the case of insurance companies that have defaulted. This research is normative juridical research that examines positive legal norms that apply in the form of laws and regulations regarding criminal acts in the financial services sector. This research is expected to provide input to OJK to immediately make improvements to the legal structure and legal culture in criminal law enforcement in the financial services sector to protect policyholders, create a healthy insurance company, and restore public trust in the insurance industry in Indonesia. In normative juridical research, the data studied are only secondary data that include primary, secondary, and tertiary legal materials. The results showed that law enforcement of criminal acts in the financial services sector in the case of insurance companies that defaulted could not be optimal due to the limited number of OJK investigator personnel, lack of knowledge and technical skills regarding criminal investigations in the financial services sector, lack of facilities, infrastructure, and funds, as well as low legal culture from insurance company managers, OJK investigators, and the public.